The Incidence and Nature of Employee Profit Sharing and Share Ownership in Canada - Long, Richard (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 1992)
This paper describes the incidence and general nature of employee profit sharing and share ownership in Canada, based on telephone interviews with chief executive officers of 626 Canadian firms conducted during 1989/90. The results indicated that there has been a dramatic growth in both of these during the past decade, despite the absence of strong legislative support, and that this growth will likely continue for some time.